2009
DOI: 10.3109/00952990903384332
|View full text |Cite
|
Sign up to set email alerts
|

D-Cycloserine and Cocaine Cue Reactivity: Preliminary Findings

Abstract: Background-D-cycloserine (DCS), a partial glutamate NMDA receptor agonist, enhances extinction of conditioned fear responding in rodents and facilitates exposure-based learning in humans with anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 17 publications
4
55
1
Order By: Relevance
“…The finding that DCS produced mild stimulant effects might suggest that it could interfere with exposurebased therapies due to state-dependent learning (Hoffman 2007). Furthermore, subjective stimulation may also increase craving and prime alcohol use, although the stimulant effect found here was not associated with enhanced response activation in our sample, in contrast to an apparent cue-activation effect in cocaine users (Price et al 2009). …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The finding that DCS produced mild stimulant effects might suggest that it could interfere with exposurebased therapies due to state-dependent learning (Hoffman 2007). Furthermore, subjective stimulation may also increase craving and prime alcohol use, although the stimulant effect found here was not associated with enhanced response activation in our sample, in contrast to an apparent cue-activation effect in cocaine users (Price et al 2009). …”
Section: Discussionmentioning
confidence: 58%
“…Therefore, examining the subjective effects of DCS in heavy drinkers (independently of exposure/response prevention) was itself a (secondary) aim of this study. Furthermore, given the description of 'response activation' to cues noted by Price et al (2009) in cocainedependent individuals receiving DCS, we also explored the possibility that this occurs in heavy drinkers receiving DCS in the presence of alcohol cues.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Cue reactivity encompasses objective measures of sympathetic arousal and/or subjective reports of craving, induced by paraphernalia or pictures associated with the abused drug. These small proof-ofconcept trials have shown decreased cue reactivity for nicotine (Santa Ana et al, 2009), no effect compared with placebo for nicotine (Kamboj et al, 2012;Yoon et al, 2013) and alcohol (Kamboj et al, 2011;Watson et al, 2011), or increased cue reactivity for cocaine (Price et al, 2009(Price et al, , 2013 and alcohol (Hofmann et al, 2012). One study that investigated clinically meaningful outcomes of D-cycloserine for augmenting cueexposure therapy found negative results for nicotine use (Yoon et al, 2013).…”
mentioning
confidence: 99%